574 Factors that influence the prescription of physical activity: a cross sectional survey: The prescription of physical activity (Balneo and PRM Research Journal, 2024)
The study aims to assess the health professionals' knowledge, attitudes, and practices toward the evaluation and prescription of PA (physical activity) to develop public health measures to improve PA preventive interventions.; Methods: A cross‐sectional study, using a confidential self‐administered questionnaire applied to health practitioners involved in individual preventive services related to PA in Romania, was conducted. The internal consistency of the questionnaire was explored, and the data were analyzed with descriptive and inferential statistics; Results: A total number of 464 health professionals (community nurses, family doctors, and other professional categories) completed all questionnaire. We found differences in knowledge distribution, with the lowest level for nurses (p